New experimental model for training in videosurgery - Batista,Danilo Malta (2012)
PURPOSE: To develop a new experimental model of lower cost for training in videosurgery. METHODS: This project was performed at the Nucleus of Experimental Surgery of the Bahiana School of Medicine and Public Health, based on previous models described in the literature and under the supervision of the full professor of Operative Technique and Experimental Surgery II. It was made a model cube-shaped, made of wood, with holes distributed in various locations, rubber stoppers for the holes and lined externally with carpet, and internally with laminate. RESULTS: The new experimental model is of low cost and reproduces quite faithfully several videosurgical procedures. CONCLUSION: Medical schools interested in the subject may adopt the new model for training in videosurgery without the need of high costs for making and using these models.